The Contemporary Use of Angiography and Revascularization Among Patients With Non–ST‐Segment Elevation Myocardial Infarction in the United States Compared With South Korea - Kang, Hyun‐Jae (Clin Cardiol, 2015)
BACKGROUND: Practice guidelines recommend an early invasive strategy for high‐risk non‐ST‐segment elevation myocardial infarction (NSTEMI) patients, but international differences in the use of invasive strategies are unknown. HYPOTHESIS: Profiling NSTEMI patient management in the United States (U.S.) and South Korea could provide insight into how patients are triaged for an early invasive strategy in different health care environments and geographical regions. METHODS: We evaluated the use of angiography and revascularization for NSTEMI patients treated at revascularization‐capable hospitals (2007–2010) in both the ACTION Registry‐GWTG (U.S.: n = 133,835; 433 hospitals) and KAMIR/KorMI Registry (South Korea: n = 7,901; 72 hospitals). RESULTS: Compared with South Korean patients, U.S. NSTEMI patients more commonly had established cardiovascular risk factors, disease, and prior cardiovascular events and procedures. From 2007–2010, the use of angiography for NSTEMI patients rose steadily in both countries, but the use of revascularization only rose in South Korea. Patients from South Korea more commonly underwent angiography and revascularization. Percutaneous coronary intervention was the most common type of revascularization in both countries, but coronary artery bypass grafting was less common in South Korea. The use of both angiography and revascularization was incrementally lower with a higher predicted mortality risk for patients from both countries, but greater differences between low‐ and high‐risk patients occurred in the U.S. CONCLUSIONS: The profile, characteristics, and use of angiography and revascularization for NSTEMI patients in the U.S. vs South Korea differed substantially from 2007–2010, underscoring the heterogeneity of NSTEMI patients and treatment selection among different countries.